Effects of mind-body exercise in chronic cardiopulmonary dyspnoea patients—a network meta-analysis of randomized controlled trials - Li, Yilin; Wu, Jing; Lei, Rong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe objective of this meta-analysis is to evaluate and compare the effectiveness of various mind-body exercises in the rehabilitation of individuals with chronic cardiopulmonary dyspnoea.DesignA systematic review and network meta-analysis was conducted on articles from PubMed, EMBASE, Cochrane Library, Web of Science, and China National Knowledge infrastructure which were searched up to November 21, 2024. The methodological quality of the included trials was evaluated using the Cochrane Risk of Bias tool. A network meta-analysis was performed to compare the effects of various mind-body therapies, including Liuzijue, Baduanjin, Yoga, Tai Chi, Wuqinxi, Qigong, Yijinjing, and Buddhist walking meditation.ResultsThe analysis included 44 randomized controlled trials involving a total of 2,957 subjects. The network meta-analysis indicated that Yoga might be the most effective exercise intervention for reducing the MLHFQ score (SUCRA: 71.8%). Yoga training demonstrated superior results in increasing the 6-minute walk distance (6MWD) (SUCRA: 99.7%). Qigong was also identified as the most effective exercise intervention for decreasing St. George's Respiratory Questionnaire (SGRQ) (SUCRA: 97.1%). When compared with other treatments, Baduanjin is likely the most appropriate intervention for decreasing COPD Assessment Test (CAT) (SUCRA: 87.1%). Regarding N-terminal pro-B-type natriuretic peptide (NT-proBNP), Yoga might be more advantageous for decreasing the NT-proBNP (SUCRA: 83.4%).ConclusionThe findings of this study suggest that mind-body exercise may represent a promising intervention for the management of chronic cardiopulmonary dyspnoea. Our findings indicate that Yoga might be the most effective exercise intervention for improving the MLHFQ scores, 6MWD, and NT-proBNP. Qigong is identified as the most effective exercise intervention for decreasing SGRQ. Compared to other treatment methods, Baduanjin may be the most suitable intervention for lowering CAT. This study recommends that patients with chronic cardiopulmonary dyspnoea select appropriate mind-body exercises to achieve effective management of chronic cardiopulmonary dyspnoea.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-11-0092/, INPLASY INPLASY2020100052.